The Influence of Leadership and Motivation on Employee Performance - Indra Januar Rukmana (Almana : Jurnal Manajemen dan Bisnis, 2020)
Human resources play an important role in company management. In this case that human resources are the main key that must be able to full attention to all their needs. Human resources are the driving force of the company. The progress of a company is very dependent on the human resources that exist in a company by giving authority and responsibility in managing activities. This study aims to determine the effect of leadership and motivation on employee performance at PT. Mitra Steel in Jakarta. The method used was explanatory research with a sample of 82 employees. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study leadership have a significant effect on employee performance by 35.2%, hypothesis testing obtained significance 0,000 <0.05. Motivation has a significant effect on employee performance by 43.1%, hypothesis testing obtained significance 0,000 <0.05. Leadership and motivation simultaneously have a significant effect on employee performance by 52.0%, hypothesis testing obtained significance 0,000 <0.05